Temporal Variation of Solar Wind in Controlling Solar Wind‐Magnetosphere‐Ionosphere Energy Budget. Issue 7 (20th July 2018) - Liu, Jing; Wang, Wenbin; Zhang, Binzheng; Huang, Chaosong; Lin, Dong
Abstract: Periodic oscillations associated with Alfven waves with periods ranging from several tens of minutes to several hours are commonly seen in the solar wind. It is not yet known how the solar wind oscillation frequency, and thus its temporal variation, regulates the energy flow through the coupled solar wind‐magnetosphere‐ionosphere‐thermosphere system. Utilizing the Coupled Magnetosphere‐Ionosphere‐Thermosphere Model driven by solar wind and interplanetary magnetic field (IMF), we have analyzed the magnetosphere‐ionosphere‐thermosphere system response to IMF B z oscillations with periods of 10, 30, and 60 min from the perspective of energy budget. Our results indicate that the energy flow from the solar wind to geospace depends on the IMF B z oscillation frequency. The energy coupling efficiency, defined as the ratio of the globally integrated joule heating to Akasofu's Epsilon function, is higher for lower frequency IMF B z oscillations. Joule heating in the upper atmosphere depends not only on directly driven processes due to solar wind variability but also on the intrinsic dynamics of the magnetosphere (i.e., loading‐unloading process). This work highlights the critical role of solar wind and IMF temporal variation and the inductive inertia and resistance of coupled magnetosphere‐ionosphere system in controlling the energy transfer in the coupled solar wind‐geospace system, which has not been explored before. Key Points: Solar wind temporal variation regulates the energy flow from the solar wind to the coupled MIT system Joule heating in the upper atmosphere depends both on the directly driven processes related to solar wind variability and the intrinsic dynamics of the magnetosphere The magnetosphere‐ionosphere‐thermosphere coupled system has a low‐pass filter nature